PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH PROVINSI MALUKU UTARA - Zulkifli Zulkifli (Jurnal Manajemen Sinergi, 2018)
The purpose of this study to determine the influence of Supervision and Discipline Work either partially  or  simultaneously  to  the  performance  of employees of the Regional Planning and Development Board of North Maluku Province. The analysis model used to test the hypothesis is multiple linear regression analysis, and research method used is explanatory research with quantitative approach and sample of 82 respondents. With data processing techniques using SPSS 16 for windows. The results of the study prove that: (1) Supervision has a positive and significant influence on Employee Performance, which means that the better the supervision the better the performance of employees. (2) Work Discipline has a positive and significant influence on Employee Performance, which means that the higher the level of discipline of employee work, the higher the level of employee performance. With the result of simultaneously both variables have positive and significant effect to Employee Performance with R2 value (R Square) corrected by 0243 or 24,3%.